2020
DOI: 10.1111/rda.13750
|View full text |Cite
|
Sign up to set email alerts
|

Xanthan gum and locust bean gum substrate improves bovine embryo development

Abstract: One of the major difference between the in vivo and in vitro embryonic environments is the stiffness of the culture substrate. Xanthan gum (XG) and locust bean gum (LBG) are natural materials that are safe, inexpensive and easy to handle. In this study, we investigated the effects of using a polysaccharide culture substrate made from 1% XG and 1% LBG (XG‐LBG gel) on bovine embryonic development. Oocytes collected from bovine ovaries were subjected to maturation, and fertilization to generate embryos at an earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…The plant-based proteins can potentially support cell adhesion, which can also be improved by aforementioned modifications [ 21 , 108 , 109 ]. Despite all this, the spatial spread of the cells may also be limited by the surrounding matrix, even if the biomaterials can support cell growth as a substrate [ 108 , 109 , 110 , 111 ].…”
Section: Resultsmentioning
confidence: 99%
“…The plant-based proteins can potentially support cell adhesion, which can also be improved by aforementioned modifications [ 21 , 108 , 109 ]. Despite all this, the spatial spread of the cells may also be limited by the surrounding matrix, even if the biomaterials can support cell growth as a substrate [ 108 , 109 , 110 , 111 ].…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of cardiac samples from our HF patients revealed increased protein levels of connective tissue growth factor (CTGF), a regulator of cardiac extracellular matrix and fibrosis [ 18 , 19 ] and a downstream effector of Yap transcriptional activity [ 20 , 21 , 22 , 23 ] ( Figure 1 F,G). To interrogate causality, we moved to mechanistic in vitro studies.…”
Section: Resultsmentioning
confidence: 99%
“…In line with this, PI3K signaling was a top enriched pathway associated with the DEGs in cumulus cells; however, whether the same mechanism works in gel–cell interaction remains unclear. Our previous report showed that embryos cultured on the XG-LGB gel upregulated actin formation and cadherin localization [ 5 ], and oocyte granulosa cell complexes derived from early antral follicles cultured on the XG-LGB gel upregulated genes associated with focal adhesion and ECM interactions [ 6 ]. Gel substrate then transfers certain signals to activate focal adhesion and ECM interaction-related molecules on cumulus cells and oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been no reports regarding the relationship between the amount of F-actin in oocytes and developmental competence, although embryos developed on XG-LBG gel showed increased levels of F-actin [ 5 ]. In the present study, either the gel culture system or TGFB1 increased F-actin formation in oocytes and improved developmental competence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation